5PSQ-133 Pharmacists – general practioners (GPs) collaboration to identify drug-related problems (DRPs) in patients in polytherapy. Issue 1 (23rd March 2023) - Mortillaro, F; Listro, A; Dominici, S; Pastorello, M
Abstract : Background and Importance: Medication reconciliation and medication review are indispensable instruments in the prevention of clinical risk. In clinical practice, such methods are not always used. This exposes the patient, in treatment transitions, to DRPs, including Adverse Drug Reactions (ADRs), which could cause his rehospitalisation. How many clinical symptoms are related to disease or hidden ADRs? The Clinical pharmacist, through remote monitoring provides, can support to the GP by a periodic analysis of the therapy taken by the individual patient. Aim and Objectives: The objective of the study was to outline a pharmaceutical care and drug monitoring methodology based on Pharmacist-GP collaboration to identify DRPs that could generate predisposing clinical conditions that can be identified as signs of hidden ADRs. Material and Methods: From April to September 2022, we established a teamwork between Pharmacists and GPs in a Local Health Authority, selecting patients >65 years of age receiving >4 drugs. Patient-related drug prescriptions on the health card were analysed, excluding herbal products, homeopathic products, and supplements. Treatment duplications, ATC therapy switches and drug interactions were examined, simultaneously verifying dosing schedules. Appointments have been set up with GPs to complement the information. Final reports were prepared for individual patient to be delivered to the GP on the clinical alerts to be monitored. Results: N.24/1304(%1, 84) GPs were involved, n. 149 patients were identified (average 72 years) and n. 1348 drugs and dosing schedules were analysed. Duplications identified: 13/1348(%0, 96). Unmotivated drug switches 23/72(%31, 94), drug alerts for interactions: n.2357. Ex. fluoroquinolone-quetiapine, statin-clopidogrel, ASA-omega-3. We identified n. 10 hidden ADRs, subsequently registered on the Pharmacovigilance National Network. Conclusion and Relevance: The identification of hidden ADRs in polytreated patients avoided the inclusion of a new drug to treat the clinical symptom not related to a new disease. The next goal is to integrate the patient into the path, a valuable source of information currently unavailable, thus implementing territorial health care through narrative pharmacovigilance that will allow a complete picture of the individual patient. The aim is to an enhanced care model with the top the patient between GP and pharmacist. References and/or Acknowledgements: Conflict of Interest: No conflict of interest